## College Algebra (10th Edition)

$\begin{array}{llll} a. & -\frac{1}{5} & e. & \frac{-2x-1}{3x-5}\\ b. & -\frac{3}{2} & f. & \frac{2x+3}{3x-2}\\ c. & \frac{1}{8} & g. & \frac{4x+1}{6x-5}\\ d. & \frac{2x-1}{3x+5} & h. & \frac{2x+2h+1}{3x+3h-5} \end{array}$
$f(x)=\displaystyle \frac{2x+1}{3x-5}$ $\begin{array}{lll} (a)\ f(0) & (b)\ f(1) & (c)\ f(-1)\quad \\ =\frac{2(0)+1}{3(0)-5} & =\frac{2(1)+1}{3(1)-5} & =\frac{2(-1)+1}{3(-1)-5}\\ =\frac{0+1}{0-5} & =\frac{2+1}{3-5} & =\frac{-2+1}{-3-5}\\ =-\frac{1}{5} & =-\frac{3}{2} & =\frac{1}{8} \end{array}$ $\begin{array}{ll} (d)\ f(-x) & (e)\ -f(x)\\ =\frac{2(-x)+1}{3(-x)-5} & =-(\frac{2x+1}{3x-5})\\ =\frac{-2x+1}{-3x-5}\quad & =\frac{-2x-1}{3x-5}\\ =\frac{2x-1}{3x+5} & \end{array}$ $\begin{array}{ll} (f)\ f(x+1) & (g)\ f(2x)\\ =\frac{2(x+1)+1}{3(x+1)-5} & =\frac{2(2x)+1}{3(2x)-5}\\ =\frac{2x+2+1}{3x+3-5} & =\frac{4x+1}{6x-5}\\ =\frac{2x+3}{3x-2} & \\ & \\ & \end{array}$ $(h)\displaystyle \ f(x+h)=\frac{2(x+h)+1}{3(x+h)-5}=\frac{2x+2h+1}{3x+3h-5}$